PENGUATAN POACE MENUJU KEMANDIRIAN DAN KESEJAHTERAAN ANGGOTA KELOMPOK TANI DAN TERNAK DI DESA RANDOTONDA PROVINSI NTT - Willybrordus Lanamana; Yohanes Pande; Laurentius Dominicus Gadi Djou; Kristono Yohanes Fowo (Universitas Muhammadiyah Mataram, 2020)
Abstrak: Tujuan pelaksanaan pengabdian kepada masyarakat di Desa Randotonda adalah untuk meningkatkan kemandirian dan kesejahteraan anggota kelompok mitra secara terpadu dan berkelanjutan, melalui kegiatan penyuluhan dan pelatihan tentang AD/ART, organisasi dan struktur organisasi, manajemen dan program kerja. Pelaksanaan pengabdian ini melibatkan dua kelompok mitra yaitu, Kelompok Tani Kema Tau Pawe dan Kelompok Ternak SeOte SeAte yang dibentuk tahun 2010 dan 2013. Metode yang digunakan, penyuluhan dan pelatihan. Pelaksanaan kegiatan diawali dengan penyuluhan, materi tentang pengertian, ciri, fungsi kelompok mitra, pengertian AD/ART, organisasi dan struktur organisasi, manajemen dan program kerja tahunan. Kegiatan pelatihan meliputi, pembuatan AD/ART, pembuatan struktur organisasi, papan nama organisasi dan pembuatan program kerja tahunan. Dari pre-test dan post-test yang diberikan terjadi peningkat nilai yang signifikan pada post-test. Pretest pada kelompok tani Kema Tau Pawe rata-rata 4,87, post-test meningkatrata-rata 13,5. Kelompok Ternak SeOte SeAte, rata-rata pre-test 5,08 post-test meningkat rata-rata 13,58. Abstract: The purpose of community service in Randotonda Village is to increase the independence and well-being of partner group members in an integrated and sustainable manner through counselling and training activities on the Articles of Association/Budget Home Appliances, organizational and organizational structure, management and work programs. The implementation of this service involved two partner groups, namely, Kema Tau Pawe Farming Group and SeOte SeAte Livestock Group which was formed in 2010 and 2013. The methods used was counselling and training. The implementation of the activity begins with counselling, materials are definition, features, functions of the partner group, understanding of Articles of Association/Budget Home Appliances, organization and organizational structure, management and annual work program. Training activities include, the creation of Articles of Association/Budget Home Appliances, the creation of organizational structures, organizational sign-ups and the creation of annual work programs. From the given pre-test and post-test there is a significant value increase on the post-test. Pre-test in Kema Tau Pawe farming group averaged 4.87, post-test increased by an average of 13.5. SeOte SeAte livestock Group, the pre-test average of 5.08 post-test increased by an average of 13.58.